Przekształcenia sacrum w polskiej literaturze fantasy - Jakubowska, Marta (My University, 2019)
Praca pt. Przekształcenia sacrum w polskiej literaturze fantasy przybliża twórczość polskich autorów i wskazuje w niej przekształcone treści zaczerpnięte ze sfery wierzeń i mitów. Przybliża warunki kształtowania się gatunku fantasy w Polsce, analizuje fenomen popularności tej literatury, jej recepcji zarówno w obrębie utworu, jak i w pozatekstowej rzeczywistości.

Work titled The transformation of the sacred in Polish fantasy literature brings closer the work of Polish authors and indicates in it transformed content taken from the sphere of beliefs and myths. It introduces the conditions for the evolution of the fantasy genre in Poland, analyzes the phenomenon of the popularity of this literature, its reception both within the song and in non-textual reality.
Transformations of the sacred in Polish fantasy literature
Wydział Filologii Polskiej i Klasycznej
Keywords: fantasy; sacrum; przekształcenia; religia; mit; sacred; transformations; religion; myth